Combined therapy in children and adolescents with classical Hodgkin's lymphoma: A report from the SFCE on MDH-03 national guidelines. (16th November 2016) - Seror, E.; Donadieu, J.; Pacquement, H.; Abbou, S.; Lambilliotte, A.; Schell, M.; Curtillet, C.; Gandemer, V.; Pasquet, M.; Aladjidi, N.; Lutz, P.; Schmitt, C.; et al.
ABSTRACT: Hodgkin's lymphoma (HL) in children and adolescents is highly curable, but children are at risk of long-term toxicity. The MDH-03 guidelines were established in order to decrease the burden of treatment in good-responder patients, and this report should be considered a step toward further optimization of treatment within large collaborative trials. We report the therapy and long-term outcomes of 417 children and adolescents treated according to the national guidelines, which were applied between 2003 and 2007 in France. The patients were stratified into three groups according to disease extension. Chemotherapy consisted of four cycles of VBVP (vinblastine, bleomycin, VP16, prednisone) in localized stages (G1/95 pts/23%), four cycles of COPP/ABV (cyclophosphamide, vincristine, procarbazine, prednisone, adriamycin, bleomycin, vinblastine) cycles in intermediate stages (G2/184 pts/44%) and three cycles of OPPA (vincristine, procarbazine, prednisone, adriamycin) plus three cycles of COPP in advanced stages (G3/138 pts/33%). Radiation therapy of the involved field was given to 97% of the patients, with the dose limited to 20 Gy in good responders (88%). With a median follow-up of 6.6 years, the 5-year event-free survival (EFS) and overall survival (OS) were 86.7% (83.1–89.7%) and 97% (94.5–98.1%), respectively. EFS and OS for G1, G2, and G3 were 98% and 100%, 81% and 97%, and 87% and 95%, respectively. Low-risk patients treated without alkylating agents and anthracycline had excellent outcomes and a low expected incidence of late effects. Intensification with a third OPPA cycle in high-risk group patients, including stage IV patients, allowed for very good outcomes, without increased toxicity.